New Discoveries at Yeavering, Northumberland - Miket, Roger; Semple, Sarah; Skinner, Tudor; Buchanan, Brian (Medieval Settlement Research, 2023)
Yeavering in Northumberland (NT926305) is well known for its appearance in the eighth-century Ecclesiastical History of the English People by the Venerable Bede. Bede describes a visit to the royal vill of Adgefrin during the reign of King Edwin (c. AD 627). During this visit he tells how the Christian missionary Paulinus ‘instructed and baptised’, in the river Glen, ‘many people who gathered there from the surrounding settlements and places’ (HE II, XIV). The site was recognised in antiquarian accounts but had largely been lost and forgotten until air photography in 1949 revealed traces of sub-surface features delineating a series of rectangular ‘hall-like’ buildings (Hope-Taylor 1977, 4).